Plateaus and Diagrams. Inside the Genocide Symbol - Sorrentino, Paolo (E|C, 2023)
In the words of one of Hamas’ key leaders, Khalil al-Hayya, the barbaric attack of October 7 should not be limited to a confrontation, but should serve to change the Israeli-Palestinian conflict. Using the idea of the (im)predictability of the plateau, our article reflects on the correlation between the actions of the East and the passions of the West, triggered by the progressive symbolic (and legal) affirmation of the genocide drama. The proposed path winds between monsters, violence, extreme spaces, genocides, massacres, individual experiences, legal definitions, political interactions, global symbols, local rubble. To conclude with a question: where is passion born? And again: is it possible to predict the future?